Development of age-dependent micronutrient centile charts and their utility in children with chronic gastrointestinal conditions at risk of deficiencies: A proof-of-concept study. Issue 4 (April 2022) - Al Fify, Maha; Nichols, Ben; Arailoudi Alexiadou, Lefkothea; Stefanowicz, Fiona; Armstrong, Janis; Russell, Richard K.; Raudaschl, Adrian; Pinto, Naina; Duncan, Andrew; Catchpole, Anthony; Galloway, Peter; Talwar, Dinesh; et al.
Summary: Background & aims: Interpretation of blood micronutrient levels requires age-appropriate reference intervals. This study developed age-dependent micronutrient centiles for healthy children (HC) and explored their utility in sick children. Methods: 244 blood samples were collected from normal HC who underwent tests for acute illness. Age-dependent, centile charts were fitted for zinc, copper, magnesium and selenium in plasma and erythrocytes (RBC), and for vitamins B1, B2 and B6 in RBC. For 34 children with Crohn's disease (CrD) and 55 with coeliac disease (CoeD), Z-scores for the levels of these micronutrients were computed, using the new charts. Associations were explored between plasma and RBC micronutrient Z-scores, and in CrD with CRP and serum albumin. Results: In HC, plasma zinc and selenium increased and plasma copper, magnesium and RBC vitamins B1, B2 and B6 decreased with age. In HC and in CrD, plasma and RBC Z-scores for copper, selenium and magnesium (all p < 0.001) were positively correlated, but not for zinc. In CrD, albumin was related with plasma zinc (rho = 0.62; p < 0.001) and selenium Z-scores (rho = 0.65; p < 0.001) and plasma copper Z-score with CRP (rho = 0.45; p = 0.02). A higher proportion of CrD children had low levels for B2 (21% vs 0%; p = 0.01) and B6 (18% vs 0%; p = 0.02) using the new centile charts than the local laboratory references. Conclusion: Age-dependent micronutrient centile charts enable tracking of micronutrient status, Z-score calculation and may prevent misdiagnosis and inappropriate treatment of deficiencies. In systemic inflammatory conditions, RBC measurements of certain micronutrients may be more reliable to use than measurements in plasma.